Angiosperms the flowering plants - EBE Corporation (Chicago : EBE Corporation, 1900)
This film describes the structural and reproductive characteristics which distinguish angiosperms from other plants. Animation and time-lapse photography are use to trace the processes of pollination, formation of seeds and fruit, seed dispersal, and plant growth in angiosperms. Illustrates a wide variety of angiosperms
Backup available in VHS 1/2 in. and DVD format
Bahan rosak (Lupus)
Keywords: Angiosperms